The Relationship between Workload and Internet Network Quality with the Completeness of Electronic Nursing Care Documentation - Musrifah Musrifah; Achir Yani Syuhaimie Hamid; Muhammad Syafwani; Lukman Harun; Mahdalena Mahdalena (GLOBAL HEALTH SCIENCE GROUP, 2025)
Electronic documentation of nursing care is an important component in ensuring service quality and patient safety. However, its implementation often faces obstacles such as high workload, limited application features, unstable internet network, and organizational policies that do not provide optimal support. This study aims to analyze the relationship between workload, nurse compliance, application features, internet network, and hospital policies with the completeness of electronic documentation of nursing care at Hospital X. This study used a quantitative approach with a cross-sectional design. The sample consisted of 76 nurses consisting of 26 outpatient nurses and 50 inpatient nurses, with an accidental sampling technique. The instruments consisted of a questionnaire and an observation sheet for completeness of documentation. Validity test results > 0.361 and reliability 0.89. Data analysis used the chi-square test and binary logistic regression. The results showed a significant relationship between completeness of documentation with the variables of workload (p = 0.001), nurse compliance (p = 0.001), application features (p = 0.001), and internet network (p = 0.001), while hospital policies were not significant (p = 0.071). Multivariate analysis showed that internet connection was the most dominant factor with an odds ratio of 29.7, followed by workload with an odds ratio of 23.7. Workload and internet connection quality are the dominant factors associated with the completeness of electronic nursing care documentation. Managerial intervention and infrastructure strengthening are needed to support the implementation of an effective documentation system.